2017
DOI: 10.1007/s00421-017-3738-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prior aerobic exercise on sitting-induced vascular dysfunction in healthy men

Abstract: Prior aerobic exercise prevented the decline in femoral artery FMD that is otherwise induced by prolonged sitting independent of changes in oxidative stress, ET-1, and NO status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(69 citation statements)
references
References 35 publications
1
53
2
Order By: Relevance
“…This lower limb vascular dysfunction as a result of prolonged sitting has conclusively been determined, in adults, to be due to alterations in shear patterns (Restaino et al 2016). Interventions focused on increasing or maintaining shear patterns before, throughout, or after prolonged sitting bouts have been successful in attenuating vascular dysfunction (Restaino et al 2015(Restaino et al , 2016Thosar et al 2015a;Morishima et al 2016Morishima et al , 2017Ballard et al 2017). Interestingly, the current study revealed no alterations in shear values throughout the 3 h sitting bout when examined as mean shear, antegrade shear, retrograde shear, or oscillatory shear index.…”
Section: Pre Mid Post Anovamentioning
confidence: 41%
See 2 more Smart Citations
“…This lower limb vascular dysfunction as a result of prolonged sitting has conclusively been determined, in adults, to be due to alterations in shear patterns (Restaino et al 2016). Interventions focused on increasing or maintaining shear patterns before, throughout, or after prolonged sitting bouts have been successful in attenuating vascular dysfunction (Restaino et al 2015(Restaino et al , 2016Thosar et al 2015a;Morishima et al 2016Morishima et al , 2017Ballard et al 2017). Interestingly, the current study revealed no alterations in shear values throughout the 3 h sitting bout when examined as mean shear, antegrade shear, retrograde shear, or oscillatory shear index.…”
Section: Pre Mid Post Anovamentioning
confidence: 41%
“…It has been demonstrated that prolonged sitting significantly alters blood flow patterns in as little as 10 min (Vranish et al 2017), primarily through reductions in mean shear values, and results in considerable macro-and microvascular dysfunction of the lower limb arteries (superficial femoral, popliteal) measured 1-3 h after the onset of sitting (Ballard et al 2017;Morishima et al 2016Morishima et al , 2017Restaino et al 2015Restaino et al , 2016Thosar et al 2015a;Vranish et al 2017). This lower limb vascular dysfunction as a result of prolonged sitting has conclusively been determined, in adults, to be due to alterations in shear patterns (Restaino et al 2016).…”
Section: Pre Mid Post Anovamentioning
confidence: 99%
See 1 more Smart Citation
“…Although previous studies administering an intervention to further reduce mean shear stress (58,68,69,85) or increase retrograde shear in the superficial femoral artery have observed a reduction in FMD (74,88,89), the perturbations were greater than the changes we observed on ascent. With respect to a vasoprotective effect of trekking, prior exercise prevents shear-mediated impairments in FMD (8,55,58). Further, two weeks of treadmill and cycle training improves popliteal artery FMD (86), thus it is possible that there was some localized training stimulus in the exercised limb that protected or offset the detrimental resting shear stress profile and other harmful stimuli (i.e.…”
Section: Flow-mediated Dilation On Ascent To High Altitudementioning
confidence: 99%
“…In 1 to 4 hours, sitting reduces vascular function by up to 4%, as measured by flow mediated dilation (FMD) (Restaino et al, 2015;Thosar et al, 2015). This reduced vascular function may be partially moderated by a systemic vasoconstrictor response, as evidenced by increased endothelin-1(ET-1) after 2 hours of sitting (Ballard et al, 2017). In addition, arterial stiffness, as measured by pulse wave velocity (PWV), increases in the lower limbs after 2 hours of standing (Caldwell et al, 2018).…”
Section: Introductionmentioning
confidence: 99%